Contextual Teaching : The Student Responses on Application Teaching Materials Using Linever (Lindo and Excel Solver) - Venissa Dian Mawarsari; Dwi Sulistyaningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Lecturers apply various models or learning strategies to the students which causes different student responses in joining the teaching learning process. However, the student responses only focus on their cognitive. It means that the lecturers only assess on the students’ achievement. Whereas the applicat ion different models or learning strategies have a purpose to achieve positive responses from the students. It is happened in learning linear program subject. In addition, there are also student responses on the teaching materials application for linear program subject based on contextual approach. Furthermore, the objective of the research is to describe student responses on the application of linear program teaching materials using contextual approach through Linever.Linever means that an acronym for Lindo and Excel Solver software. Moreover, textbook and student’ worksheets (LKM) are the teaching materials which are developed. The technique of data collection uses student responses questionnaires. The result of the research is the student responses on the linear program materials using contextual approach through Linever got 96.6%. In conclusion, this research had achieved the positive responses from the students in learning linear program subject. Keywords: Contextual Teaching, Student Response, Teaching Materials, Lindo and Excel Solver